Analysis of Fiscal Decentralization, Human Development Index, and Income Inequality on Poverty Levels in Sampang Regency - Syamsul Huda (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
Poverty remains a major development challenge in Indonesia, particularly in regions experiencing persistent socioeconomic disparities, such as Sampang Regency. Although fiscal decentralization provides greater authority for local governments to manage regional resources, its effectiveness in reducing poverty depends on the quality of budget allocation, human development conditions, and income distribution. This study aims to examine the effects of fiscal decentralization, the Human Development Index (HDI), and income inequality on poverty levels in Sampang Regency. This research employed a quantitative approach with an explanatory research design. The study utilized secondary data obtained from official sources, including regional financial reports and statistical publications covering the period from 2015 to 2024. Data analysis was conducted using multiple linear regression analysis, supported by classical assumption tests, F-tests, and t-tests to evaluate the relationships between the independent and dependent variables. The results indicate that fiscal decentralization and HDI have significant negative effects on poverty levels, suggesting that effective fiscal management and improvements in education, healthcare, and living standards contribute to poverty reduction. Meanwhile, income inequality has a significant positive effect on poverty levels, indicating that unequal income distribution increases vulnerability among disadvantaged communities. Simultaneously, fiscal decentralization, HDI, and income inequality significantly influence poverty levels in Sampang Regency. This study concludes that poverty alleviation requires integrated policies emphasizing efficient fiscal governance, human capital development, and inclusive economic growth.